Divergent Resorbability and Effects on Osteoclast Formation of Commonly Used Bone Substitutes in a Human In Vitro-Assay - Keller, Johannes; Brink, Silja; Busse, Björn; Schilling, Arndt F.; Schinke, Thorsten; Amling, Michael; Lange, Tobias (PLOS ONE, 2012)
Bioactive bone substitute materials are a valuable alternative to autologous bone transplantations in the repair of skeletal defects. However, clinical studies have reported varying success rates for many commonly used biomaterials. While osteoblasts have traditionally been regarded as key players mediating osseointegration, increasing evidence suggests that bone-resorbing osteoclasts are of crucial importance for the longevity of applied biomaterials. As no standardized data on the resorbability of biomaterials exists, we applied an in vitro-assay to compare ten commonly used bone substitutes. Human peripheral blood mononuclear cells (PBMCs) were differentiated into osteoclasts in the co-presence of dentin chips and biomaterials or dentin alone (control) for a period of 28 days. Osteoclast maturation was monitored on day 0 and 14 by light microscopy, and material-dependent changes in extracellular pH were assessed twice weekly. Mature osteoclasts were quantified using TRAP stainings on day 28 and their resorptive activity was determined on dentin (toluidin blue staining) and biomaterials (scanning electron microscopy, SEM). The analyzed biomaterials caused specific changes in the pH, which were correlated with osteoclast multinuclearity (r = 0.942; p = 0.034) and activity on biomaterials (r = 0.594; p = 0.041). Perossal led to a significant reduction of pH, nuclei per osteoclast and dentin resorption, whereas Tutogen bovine and Tutobone human strikingly increased all three parameters. Furthermore, natural biomaterials were resorbed more rapidly than synthetic biomaterials leading to differential relative resorption coefficients, which indicate whether bone substitutes lead to a balanced resorption or preferential resorption of either the biomaterial or the surrounding bone. Taken together, this study for the first time compares the effects of widely used biomaterials on osteoclast formation and resorbability in an unbiased approach that may now aid in improving the preclinical evaluation of bone substitute materials.